2018
DOI: 10.3390/ijms19010243
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping for Fiber Quality and Yield Traits Based on Introgression Lines Derived from Gossypium hirsutum × G. tomentosum

Abstract: The tetraploid species Gossypium hirsutum is cultivated widely throughout the world with high yield and moderate fiber quality, but its genetic basis is narrow. A set of 107 introgression lines (ILs) was developed with an interspecific cross using G. hirsutum acc. 4105 as the recurrent parent and G. tomentosum as the donor parent. A specific locus amplified fragment sequencing (SLAF-seq) strategy was used to obtain high-throughput single nucleotide polymorphism (SNP) markers. In total, 3157 high-quality SNP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…They used the SLAF-seq method to obtain SNP markers. In this study, 74 QTLs and five clusters were found that were related to various fibre quality parameters (Keerio et al 2018). Islam and co-workers have detected and validated 5 617 SNPs in upland cotton using GBS (Islam et al 2015).…”
Section: Reporting Of Snps/qtls In Cotton Fibre Quality and Yield Traitsmentioning
confidence: 74%
“…They used the SLAF-seq method to obtain SNP markers. In this study, 74 QTLs and five clusters were found that were related to various fibre quality parameters (Keerio et al 2018). Islam and co-workers have detected and validated 5 617 SNPs in upland cotton using GBS (Islam et al 2015).…”
Section: Reporting Of Snps/qtls In Cotton Fibre Quality and Yield Traitsmentioning
confidence: 74%
“…The non-domesticated allotetraploid species (G. tomentosum, G. mustelinum, and G. darwinii) have also been widely utilized in genetic mapping programs for the improvement of fiber quality traits (Keerio et al, 2018). The interspecific population between G. hirsutum and G. mustelinum (AD 4 ) demonstrated potential value in cotton breeding programs for the improvement of fiber quality (Wang et al, 2017).…”
Section: Potential Qtls Mapped For Key Fiber Quality Traitsmentioning
confidence: 99%
“…Several QTLs were detected across two environments in a RIL population by a genetic map harboring 2618 SNP markers for fiber quality traits and identified 12 QTLs for fiber length and 8 QTLs for fiber strength . A SLAF-seq genetic mapping study conducted with 107 ILs from G. tomentosum, identified 30 QTLs linked with fiber quality traits (Keerio et al, 2018). The CottonSNP80K array was utilized for a GWAS study combined with RNA-seq analysis of fiber development stages to predict several candidate genes with differential expression patterns (Dong et al, 2019).…”
Section: Potential Qtls Mapped For Key Fiber Quality Traitsmentioning
confidence: 99%
“…Seventy-four QTLs were detected to be associated with ve ber quality traits (30 QTLs) and eight yield traits (44 QTLs) using 107 introgression lines, which were developed with an interspeci c cross using G. hirsutum acc. 4105 as the recurrent parent and G. tomentosum as the donor parent (Keerio et al 2018). One hundred and eighty-six additive QTLs were obtained for ve ber quality traits using 137 recombinant inbred lines (Jia et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 884 QTLs associated with cotton ber traits from 12 studies (Ali et al 2018;Diouf et al 2018;Huang et al 2017;Jia et al 2018;Keerio et al 2018;Li et al 2016a;Liu et al 2018b;Ma et al 2018a;Tan et al 2018;Wang et al 2015;Zou et al 2018) were used for meta-QTL analysis based on upland cotton reference genome TM-1 (Zhang et al 2015a), and 74 meta-QTLs were identi ed. Combined with 8589 signi cant SNP loci associated to cotton ber quality traits collected from 15 previous publications (Chandnani et al 2018;Fang et al 2017;Gapare et al 2017;Handi et al 2017;Huang et al 2017;Islam et al 2016;Li et al 2017b;Liu et al 2018b;Ma et al 2018a;Ma et al 2018b;Su et al 2016;Su et al 2018;Sun et al 2017;Wen et al 2018), 297 candidate genes associated with cotton ber quality traits were identi ed.…”
Section: Introductionmentioning
confidence: 99%